2022
DOI: 10.1051/0004-6361/202243664
|View full text |Cite
|
Sign up to set email alerts
|

Fast time optical variability in Be/X-ray binaries

Abstract: Context. Classical Be stars, regardless of spectral subtype, display multiperiodic light modulations in the frequency range 0.1-12 c d −1 , when observed with high-cadence and long duration. This behaviour is attributed to non-radial pulsations and/or rotation of the Be star. A similar study for the optical counterparts to Be/X-ray binaries is yet to be carried out. Aims. The main goal of this work is to investigate the fast photometric variability of the optical counterparts to Be/X-ray binaries and compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 199 publications
(264 reference statements)
1
3
0
Order By: Relevance
“…Our study of KS 1947+300 emphasizes the variable nature of BeXBs in the optical band on all time scales: long (years) as shown in Sect. 3.1, intermediate (weeks to months) as shown in this section, and short (hours to days) as shown by Reig & Fabregat (2022).…”
Section: Periodic Signals In Ztf-g and R Band Light Curvessupporting
confidence: 56%
See 1 more Smart Citation
“…Our study of KS 1947+300 emphasizes the variable nature of BeXBs in the optical band on all time scales: long (years) as shown in Sect. 3.1, intermediate (weeks to months) as shown in this section, and short (hours to days) as shown by Reig & Fabregat (2022).…”
Section: Periodic Signals In Ztf-g and R Band Light Curvessupporting
confidence: 56%
“…Kızıloglu et al (2007) performed optical photometry of KS 1947+300 with high cadence and found an increase of about 0.1 mag in coincidence with and increase in the X-ray flux from quiescence to 5 × 10 36 erg s −1 , typical behavior of a type I outburst. Other works that report optical observations of KS 1947+300 in the context of a global study of the optical properties of BeXBs are given in Reig & Fabregat (2015), Reig et al (2016), and Reig & Fabregat (2022).…”
Section: Introductionmentioning
confidence: 99%
“…The massive companion is a long-term variable system with photometric and spectroscopic changes on timescales of years (Kızıloǧlu et al 2007;Reig & Fabregat 2015;Reig et al 2016). The underlying B star also displays fast optical multiperiodic variability that is attributed to nonradial pulsations (Kızıloǧlu et al 2007;Reig & Fabregat 2022). We present the most complete and detailed study of the optical variability of the BeXB GRO J2058+42 performed so far.…”
Section: Introductionmentioning
confidence: 96%
“…The massive companion is a long-term variable system with photometric and spectroscopic changes on timescales of years (Kızıloǧlu et al 2007;Reig & Fabregat 2015;Reig et al 2016). The underlying B star also displays fast optical multiperiodic variability that is attributed to nonradial pulsations (Kızıloǧlu et al 2007;Reig & Fabregat 2022). We present the most complete and detailed study of the optical variability of the BeXB GRO J2058+42 performed so far.…”
Section: Introductionmentioning
confidence: 99%